(untitled) (Indian Journal of Animal Production and Management, 2013)
An investigation was undertaken to study the motivational factors related to piggery farming in Kamrup district of Assam. The study was conducted in two purposively selected development blocks namely Rampur and Chayani- Barduar development block. Majority of the respondents, 64 per cent belonged to middle age group (28-38 years). 52 per cent of them belonged to ‘Schedule Tribe’ caste. 27 per cent educational qualifications were up to HSLC. Majority of the respondents, 42 per cent came from families having family size of 6 and above. Most of the respondents i.e. 94 per cent had nuclear type of families. Agriculture was the major occupation of about 79 per cent of the respondents. Only 11 per cent of the respondents had under gone training on pig farming. 48 per cent of the farmers had been rearing pigs for 5 to 7 years. Annual income from pig farming for majority 40 per cent of the respondents were (Rs.21, 000 to Rs. 28,000). As far as total annual income from all sources is concerned, majority 74 per cent were in medium category (Rs.54, 000 to 73,000). Majority of the respondents, 38 per cent reared more than 6 numbers of pigs. Total average annual income from pig farming was Rs. 24,950.00. Huge demand of pork in the markets, scope to start with small scale, to earn additional income, less capital investment, multiple rearing per year, to become self-reliant and less reliance on outside labour were some of the factors that motivated the respondents to take up pig farming.